2020
DOI: 10.3390/ani10020351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Physical Properties of Bedding Materials for Dairy Cattle Using Fuzzy Clustering Analysis

Abstract: The bedding materials used in dairy cow housing systems are extremely important for animal welfare and performance. A wide range of materials can be used as bedding for dairy cattle, but their physical properties must be analysed to evaluate their potential. In the present study, the physical properties of various bedding materials for dairy cattle were investigated, and different fuzzy clustering algorithms were employed to cluster these materials based on their physical properties. A total of 51 different be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Using engineered stand-off pads (Figure 1), the farmer can control the amount of animal effluent deposited onto the soil and return the collected effluent onto fields over at a rate that maximises pasture growth and minimises NO − 3 leaching (Luo et al, 2004). The surface area of stand-off pads is often covered with different types of bedding (Ferreira Ponciano Ferraz et al, 2020), including wood materials, such as wood chips, bark chips or sawdust. The bedding material in stand-off pads has to be regularly replaced as cows avoid resting in wet or waterlogged material (Longhurst et al, 2013).…”
Section: Stand-off Pads In Agricultural Systemsmentioning
confidence: 99%
“…Using engineered stand-off pads (Figure 1), the farmer can control the amount of animal effluent deposited onto the soil and return the collected effluent onto fields over at a rate that maximises pasture growth and minimises NO − 3 leaching (Luo et al, 2004). The surface area of stand-off pads is often covered with different types of bedding (Ferreira Ponciano Ferraz et al, 2020), including wood materials, such as wood chips, bark chips or sawdust. The bedding material in stand-off pads has to be regularly replaced as cows avoid resting in wet or waterlogged material (Longhurst et al, 2013).…”
Section: Stand-off Pads In Agricultural Systemsmentioning
confidence: 99%
“…In recent years, the use of cereal straw has also become interesting for various industries and agriculture. Apart from the classic use in agriculture as a bedding material [38], its application can be very versatile, e.g., packaging material [39]. New forms of straw use are being sought, for example, in construction as an insulating material [40,41].…”
Section: Present Timementioning
confidence: 99%
“…Research conducted by Fregonesi et al [ 14 ] showed the impact of bedding material quality, i.e., sand moisture on cow preferences and lying time. In addition to sand, the research covers other, alternative bedding materials, and the recognition of the properties of these materials allows for their proper selection in terms of the welfare requirements of dairy cattle [ 15 ]. When assessing the lying area, studies with cows also take into account the features of other technical equipment in barns, including stall partitions (typical for a tie-stall and freestall system) [ 16 ] and brisket board (typical for a freestall system) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%